Development of the Bisphenol A exposure scale in adults - Kaplan, Betül; Ortabağ, Tülay; Aslan, Ekrem (Frontiers in Public Health, 2024)
ObjectiveThis study was conducted to develop a scale for assessing the attitudes of adults regarding the determination of Bisphenol A exposure.MethodsThe study sample comprised of 370 individuals who volunteered to participate. According to the Explanatory Factor Analysis (EFA) results of the investigation, a scale structure consisting of a total of 3 sub-dimensions was obtained. In the Confirmatory Factor Analysis, the scale item factor loading values were acceptable.ResultsThe fit indices for the scale were CMIN/df = 1,618, RMSEA = 0.058, NFI = 0.914, CFI = 0.965, and IFI = 0.790, indicating a satisfactory level of agreement. The scale was determined to have a Cronbach value of 0.79 and a high degree of reliability. The item-total score correlation coefficients of the scale ranged from 0.327 to 0.534 and exhibited a high degree of discrimination, as determined.ConclusionBased on the analyses conducted, it was determined that the Adult Bisphenol A Exposure Scale is a valid and reliable instrument for determining the attitudes of adults toward contact with and use of Bisphenol A-containing products.